2012
DOI: 10.1108/10610421211215418
|View full text |Cite
|
Sign up to set email alerts
|

Does advertising matter to store brand purchase intention? A conceptual framework

Abstract: PurposeThe hottest trend in retailing is the emergence of “premium” store brands. Though store brands are treated as important players in grocery store strategies, many retailers prefer price over quality and often prefer to invest in store promotion, while neglecting brand advertising. This paper's aims are to propose a conceptual framework, integrating advertising‐related psychographic factors which will be empirically tested.Design/methodology/approachData were collected through a survey of 206 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 49 publications
0
19
0
6
Order By: Relevance
“…Insufficient investment in the advertising of PL products can lead to improper familiarity or undesired emotion towards PL products, particularly among 'high' advertising lover consumers, who tend to rely highly on advertising as regards their brand perception and preferences (Levy and Gendel-Guterman 2012). Moreover, it was also found that non-user perceptions of PL show deviations from normal patterns.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Insufficient investment in the advertising of PL products can lead to improper familiarity or undesired emotion towards PL products, particularly among 'high' advertising lover consumers, who tend to rely highly on advertising as regards their brand perception and preferences (Levy and Gendel-Guterman 2012). Moreover, it was also found that non-user perceptions of PL show deviations from normal patterns.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Dengan adanya advertising akan membantu menciptakan brand awareness (kesadaran merek) dan brand image (citra merek). Secara umum advertising cenderung bersifat ditujukan kepada banyak orang dan ratarata berbiaya tinggi (Levy dan Gendel-Guterman, 2012).…”
Section: Advertisingunclassified
“…Fitzell, ; Quelch and Harding, ) found quality perceptions of store brands significantly improved, while some recent studies (e.g. Levy and Gendel‐Guterman, ) postulate that a store brand's perceived quality is nowadays the most important factors in predicting purchase intention.…”
Section: Literature Review and Research Aimsmentioning
confidence: 99%
“…A common strategy of manufacturer brands to defend against rising market shares of store brands is sales promotions (Ailawadi et al ; Levy and Gendel‐Guterman, ). However, while some past studies (e.g.…”
Section: Literature Review and Research Aimsmentioning
confidence: 99%
See 1 more Smart Citation